2022
DOI: 10.3389/fevo.2022.813600
|View full text |Cite
|
Sign up to set email alerts
|

Reconsidering the “War on Rats”: What We Know From Over a Century of Research Into Municipal Rat Management

Abstract: To sustainably control urban rat infestations, management efforts need to encompass large areas of urban centers. Therefore, the objective of this review and narrative synthesis was to collate what is known about municipal-scale rat management. We explored the management frameworks that have been used at a large scale in cities and we describe the expectations of experts who have designed and implemented these frameworks. We found that there has been a persistent “war on rats” paradigm driving this literature … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 64 publications
0
12
0
Order By: Relevance
“…In that context, and viewed more broadly, if the wider goal of urban ecology is to plan for a future where urban environments are habitats for people and animals to thrive together ( 24 , 80 83 ), then basing those plans on perspectives from smaller scale, recent timeframes could put us at a disadvantage. Moreover, given the challenges of excluding rodents from urban spaces ( 78 ), rats will almost certainly have a place in that planned-for-future. It therefore stands to reason that building urban ecological plans on retrospectives that span hundreds or thousands of years, incorporating the tremendous range of human urban development, rather than observations from the past few decades, will create more robust strategies and approaches for urban planning.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In that context, and viewed more broadly, if the wider goal of urban ecology is to plan for a future where urban environments are habitats for people and animals to thrive together ( 24 , 80 83 ), then basing those plans on perspectives from smaller scale, recent timeframes could put us at a disadvantage. Moreover, given the challenges of excluding rodents from urban spaces ( 78 ), rats will almost certainly have a place in that planned-for-future. It therefore stands to reason that building urban ecological plans on retrospectives that span hundreds or thousands of years, incorporating the tremendous range of human urban development, rather than observations from the past few decades, will create more robust strategies and approaches for urban planning.…”
Section: Discussionmentioning
confidence: 99%
“…In the context of rat ecology, while there has been an explosion of publications in the recent literature, relatively little attention is given to the relative impacts of the two species (i.e., the implications of whether black, brown, or both rat species are present) on human health, wildlife, and the economy. Among the many contemporary ecological syntheses published in the past 5 years [e.g., (25,(76)(77)(78)(79)], for instance, none review evidence in relation to taxonomic occurrence across broader spatial (e.g., urban versus rural, populations density, regional climate, and governance geography) or temporal scales [though see (27)] or how this parameter affects human health, wildlife outcomes, or the economic costs of sharing urban spaces with rodents. In this context, most discussion has focused either on rats irrespective of taxon or on the dominant brown rat.…”
Section: Broader Trends and Implicationsmentioning
confidence: 99%
“…For example, the predominant aim of these programs is to reduce rats in as many outdoor spaces as possible [ 22 , 26 , 27 ]. In contrast, this study found that rats were more likely to be a primary concern when they were in or around someone’s living space, areas that may be the least likely to be addressed by these municipal programs [ 12 , 13 ]. This indicates that municipal rat management strategies would better serve their communities by targeting rat control efforts to specific instances in which the hazards posed by rats are perceived to be highest, including in and around places where people live.…”
Section: Discussionmentioning
confidence: 99%
“…Understanding why people are concerned about rats is important for the development of effective rat management strategies. This is because municipal rat management programs are designed to be a service to their communities and therefore they must be responsive to resident concerns to effectively meet their needs [ 12 , 13 ]. However, there is limited published information available on the specific reasons that urban residents care about rats and where, when, and what they want municipal governments to do about them.…”
Section: Introductionmentioning
confidence: 99%
“…Integrated interventions designed to address deeper-seeded issues at the crux of a problem like conflicting values and social and political inequities, are what is called for when facing wicked problems. Lee et al (2022) suggested that the global management of urban rats is a wicked problem, and strategies employed to sustainably manage these commensals must comprehensively map the extent of infestations and their underlying social, economic and political causes. Approaching the rat problem by confronting upstream determinants will likely lead to multiple concurrent options that will serve to make incremental gains in the problem over time.…”
Section: Harm Reduction Principlementioning
confidence: 99%